VD_FINDINFO HC / 2015 / 362 vom 23. April 2015 - VD Tribunal cantonal (2015)
COMPÉTENCE RATIONE MATERIAE, CONNEXITÉ MATÉRIELLE, VALEUR LITIGIEUSE | 308 CPC (CH), 59 al. 1 CPC (CH), 59 al. 2 let. b CPC (CH), 91 al. 1 CPC (CH)